If the equation be y = x² + 4 then the inverse function be [tex]f^{-1} (x)=[/tex] ± [tex]\sqrt{x - 4[/tex]
An inverse function, also known as an anti function, is a function that can be reversed into another function. Simply put, if any function " f " takes x to y, then its inverse will take y to x. The inverse function is denoted by f-1 or F-1 if the function is denoted by ' f ' or ' F '.
Let the equation be y = x² + 4
then the function be f(x) = x² + 4
y = x² + 4
⇒ x = y² + 4
simplifying the above equation, we get
x - 4 = y²
√y² = √x - 4
The value of y = ± √x - 4
Therefore, the inverse function be [tex]f^{-1} (x) =[/tex] ±√x - 4
To learn more about inverse function, refer to:
brainly.com/question/25289437
#SPJ